Fatwa Mui No. 75 Tahun 2009 Sebagai Formula Terhadap Stigma Masyarakat Anti MLM (Multi Level Marketing) - Zahra, Zahra (Universitas Tabanan, 2023)
The development of the times makes a business develop rapidly by using various kinds of marketing and one of them is Multi Level Marketing or what is usually interpreted as multi-level marketing or multi-level marketing. Most companies consider that Multi Level Marketing can bring profits if this system is implemented in them. However, as time progressed, Indonesian society perceived Multi Level Marketing as a business that could be detrimental to its members and this perception gave birth to the anti-MLM movement. And the results of this research explain that the public stigma that gave birth to the anti-MLM movement was due to the emergence of Money Game companies masquerading as Multi-Level Marketing companies. For this reason, the fatwa of the Indonesian Ulema Council no. 75 of 2009 exists as a guideline for the Indonesian people, the majority of whom follow the Islamic religion, to be able to differentiate between the provisions for implementing Sharia Multi Level Marketing and the Money Game. And the method used in this research is by using a literature method taken through previous research and then analyzed using MUI Fatwa No. 75 of 2009.